Nursing students’ experiences of clinical competency evaluation in a pre-registration nurse education programme: A qualitative study - Sitwira, Joseph; Ashipala, Daniel O.; Katjimune, Vaja (Curationis (Pretoria), 2025)
Background The evaluation of clinical competence is a diverse, rigorous procedure that determines a student’s clinical competence. Despite this, little research exists on nursing students’ experiences with clinical competency evaluations in Namibia. Nurse educators should thus explore nursing students’ experiences of clinical competency evaluations in order to establish what challenges they face, as this can be beneficial for nurturing a positive learning environment. Objectives This research assesses nursing students’ experiences of clinical competency evaluations in a pre-registration nurse education programme at the Faculty of Health Sciences in Namibia, University of Namibia, Rundu campus. Method The study was conducted at a public nurse education institution in Namibia. A qualitative approach was employed utilising an exploratory, contextual and descriptive design. This study was conducted from August 2023 to October 2023 among (second-, third- and fourth-year) nursing students who were enrolled for a Bachelor of Nursing Science (Clinical) (Honours) degree. Data were collected through semi-structured interviews with 16 nursing students being selected using a convenience sampling method. All interviews were audio recorded and transcribed verbatim. A thematic analysis method was utilised to analyse the data. Results Three themes emerged in this study: (1) positive experiences of evaluation for clinical competence; (2) negative experiences of evaluation for clinical competence and; (3) recommendations to improve the clinical evaluation of competence. Conclusion The results showed that nursing students had both negative and positive experiences during the clinical assessment process. The positive experiences included integrating theory and practice, while negative experiences included the poor attitudes of the clinical evaluators and limited time. Contribution The results of this study can be used to develop targeted interventions and strategies to improve the challenges students encounter during clinical assessment.